Patterns of Non-Communicable Disease Comorbidities among Older Persons in Bangladesh (Social Science Review, 2025)
Comorbidity among older adults is a significant public health concern in Bangladesh. This study investigated the patterns and correlates of non- communicable disease comorbidities among older persons in Bangladesh through a cross-sectional study carried out in Dhaka and Chittagong divisions among people aged 60 years and above who suffered from any non-communicable disease in the past three months of the survey. Data was collected from 474 respondents. Descriptive statistics, chi-squared tests, and independent sample t- tests were used to explore the non-communicable disease comorbidities among respondents. The findings showed that the majority of the respondents were suffering from diabetes (39.2 percent), arthritis (38 percent), high blood pressure (34.6 percent), ulcer (26.4 percent), asthma (20.9 percent), and kidney diseases (20.3 percent) and were significantly suffering from several comorbidities like arthritis and ulcer (16.5 percent), arthritis and high blood pressure (15.6 percent), high blood pressure and diabetes (24.5 percent), and diabetes and asthma (11.8 percent) at the same time. Results showed that comorbidity of high blood pressure and diabetes was higher among the 60-70 age group, comorbidity of arthritis and ulcer was higher among rural respondents, comorbidity of diabetes and asthma was higher among males, comorbidity of arthritis and ulcer was higher among educated respondents, and comorbidity of high blood pressure and diabetes was higher among those who had a monthly income source. The study suggests that the government should improve primary healthcare by integrating non-communicable disease-related services and developing physical and human resources, focusing on promoting healthy lifestyles among older persons.Social Science Review, Vol. 41(1), June 2024, Page 1-16.